Teaching and evaluating affective attributes in the dental curriculum perceptions and practices of teachers and students of the UP College of Dentistry - Apolinario-Poblete, Melissa A. (2001)
The profession of dentistry call for certain affective attributes in its members such as professionalism, compassion, ethics and life-long learning. Do dental educators teach students to develop these attributes? At the University of the Philippines College of Dentistry, the faculty and the senior and resident classes of dental students were surveyed regarding their perceptions on the inclusion of affective attributes in the curriculum and on the instructional practices used by the faculty in teaching them. There were forty-two faculty respondents, who represented all the courses in the curriculum except for five courses. The survey of the faculty showed that all faculty except one (97.6%) thought that attitudes and values should be part of the curriculum. The faculty ranked the attribute "honesty" highest in importance, followed by "caring for the patient", "discipline" and "love for God". Majority (92.9%) thought values should be included in the subjects they teach, while 88.2 replied that they would want to teach attitudes and values to their students. However, only 73.8 actually taught attitudes and values in their subject. When asked about the frequency of teaching attitudes and values, it was reported as "always" = 14.63%, "often"=26.8%, "sometimes" = 41.5% , "rarely" = 17% and "never" = 0% . A small number of respondents (22.5%) included attitudes and values in their written course objectives, and the most frequently cited were: "caring for the patient", "preparedness", "cleanliness", and "being considerate of patients' feelings. The teachers, however, also cited attitudes and values that they teach but which are not written in their course objectives, and the top four were: "honesty", "caring", "lifelong learning" and "discipline". The most frequently cited strategies to teach attitudes and values were anecdotes or stories during lectures, case discussions, use of analogues and through checking attendance. Only half of the respondents (52.4%) reported that attitudes are part of the evaluation criteria for student performance in their subjects. The most commonly cited attributes were cleanliness, preparedness, promptness and caring for the patient. But only 35.7% of the respondent reported that they had an assessment tool for attitudes. The most commonly cited assessment tools were the use of clinical or laboratory performance checklists/rating scales, and checking attendance. Majority of the faculty (90.5%) said that they experience problems in teaching attitudes and values, with frequency reported as: always=2.6% , often=15.79% , sometimes=50% , while 5.3% rarely experienced problems. Many faculty (n=9) cited "the presence of pre-set attitudes and values in students" most often as a problem in teaching affective attributes. With regard to evaluating attitudes, the most often cited problems in evaluating attitudes was the lack of assessment tools, and how to grade attitudes and values learned. Majority (88%) however were willing to learn more about teaching attitudes and values; and 85.7% were also willing to learn more about evaluating attitudes. The survey of the student?s (response rate=60.6%, number of respondents=40) showed that almost all students (95%) except two think that attitudes and values should be part of the curriculum. The students ranked the attribute "caring for the patient" highest importance, followed by, "discipline", "love for God", and "honesty". These are the same top four attributes ranked by the faculty though the order is different, showing a similarity in values of the faculty and students. Majority of the students thought they learned attitudes and values as a result of their dental education (87.5%). The most frequently cited attitudes and values students thought they learned as a result of their dental education were "caring for the patient", "being considerate of patients" "feelings", "cleanliness", "life-long learning" and "preparedness". Only 25% thought that their teachers were able to teach them attitudes and values in all the courses in the curriculum. Among all the courses, the most frequently cited subject where the students think they learned attitudes and values was Clinical Prosthodontics. With regard to the students' perception of the frequency that their teachers taught them attitudes and values, it was reported as: "always"=2.5% , "often"=35% , "sometimes"=50% , and "rarely"=10% . The students remembered anecdotes and stories during lectures as the strategy for teaching attitudes and values that their teachers used most often. This was also the strategy that the students liked most. When asked if they perceived their teachers as role models, only 62.5% did perceive their teachers as such, 20% did not while 12.5% answered that they only perceived some teachers as role models. When asked if they thought that attitudes should be emphasized more in dental education, 90% of the respondents answered in the affirmative. The Likert-type questionnaire administered to the students showed that for all the 30 questions, which represent all the affective attributes heretofore listed in the faculty and student questionnaires, generally showed a pattern of responses consistent with the listed desired affective attributes, with majority giving the expected answers, except for three items which had answers spread across the spectrum of the scale. The primary recommendations arising from the results of the research pertain to curriculum development. These recommendations are for including core values in the curriculum, the identification of the desired affective attributes from UPCD graduates, for purposeful teaching and thoughtful evaluation of affective attributes in all the courses in the curriculum, for designing an appropriate faculty development program for the teaching and evaluating of affective attributes, and most importantly for a commitment from the faculty to consciously role-model the chosen affective attributes to their students.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Affective attributes